The role of graphene loading on the corrosion-promotion activity of graphene/epoxy nanocomposite coatings. (15th September 2019) - Sun, Wen; Wu, Tingting; Wang, Lida; Yang, Zhengqing; Zhu, Tianzhen; Dong, Chuang; Liu, Guichang
Abstract: It is still arguable whether graphene/polymer nanocomposite coating is corrosion inhibitors or promoters. This work aims to determine the "percolation threshold" for corrosion-promotion activity of the graphene/polymer nanocomposite coating. Graphite oxide is partially reduced by Fe powder-induced hydrogen bubbling, followed by rapid microwave-assisted thermal reduction. Graphene/epoxy nanocomposite coating is fabricated by dispersing the graphene nanosheets into epoxy matrix with the help of ball milling. Localized electrochemical technologies are employed to investigate the corrosion behaviour of metal substrate at artificial defects of the graphene/epoxy nanocomposite coating. Experiments reveal that epoxy coating loading with more than 0.1 vol% of graphene exhibits a noticeable corrosion-promotion activity when the coating is mechanically damaged. Graphical abstract: Image 1 Highlights: Graphene is prepared by a cost-effective method. Copper corrosion at a defect of graphene-based coating is study. Percolation threshold for corrosion promotion activity of graphene/epoxy coating is 0.1 vol%.